Echoes of a lost justice - Abdul Razak, Mohd Abbas (Center for Community Development and Education (CCDE) Banda Aceh, 2025)
In a world so divided by wealth, power, race, and ideologies, I did not find justice. The very people who should uphold justice are sliding away, siding instead with those seated in positions of power. From the Third World to the most advanced countries, I did not witness justice. Justice is missing not only in ordinary courthouses but even at the United Nations. Human rights, freedom, and independence have become privileges enjoyed only by rich and powerful nations. The voices of the poor, oppressed, and marginalized communities are neither fairly heard nor adequately represented at the UN.